Willingness-to-pay for a COVID-19 vaccine and its associated determinants in Indonesia - Harapan Harapan; Abram L. Wagner; Amanda Yufika; Wira Winardi; Samsul Anwar; Alex Kurniawan Gan; Abdul M. Setiawan; Yogambigai Rajamoorthy; Hizir Sofyan; Trung Quang Vo; Panji Fortuna Hadisoemarto; Ruth Müller; et al. (Taylor & Francis Group, 2020)
How countries, particularly low- and middle-income economies, should pay the coronavirus disease 2019 (COVID-19) vaccine is an important and understudied issue. We undertook an online survey to measure the willingness-to-pay (WTP) for a COVID-19 vaccine and its determinants in Indonesia. The WTP was assessed using a simple dichotomous contingent valuation approach and a linear regression model was used to assess its associated determinants. There were 1,359 respondents who completed the survey. In total, 78.3% (1,065) were willing to pay for the COVID-19 vaccine with a mean and median WTP of US$ 57.20 (95%CI: US$ 54.56, US$ 59.85) and US$ 30.94 (95%CI: US$ 30.94, US$ 30.94), respectively. Being a health-care worker, having a high income, and having high perceived risk were associated with higher WTP. These findings suggest that the WTP for a COVID-19 vaccine is relatively high in Indonesia. This WTP information can be used to construct a payment model for a COVID-19 vaccine in the country. Nevertheless, to attain higher vaccine coverage, it may be necessary to partially subsidize the vaccine for those who are less wealthy and to design health promotion materials to increase the perceived risk for COVID-19 in the country.